A novel missense mutation within the domain of lysine demethylase 4D (KDM4D) gene is strongly associated with testis morphology traits in pigs. Issue 1 (2nd January 2020) - Zhou, Tong; Wei, Hancheng; Li, Dairui; Yang, Wenjing; Cui, Yang; Gao, Jiayang; Yu, Ting; Lv, Xiaoyan; Pan, Chuanying
Abstract: Lysine demethylase 4D ( KDM4D ) encodes a histone demethylase, which can influence the androgen signaling as well as play an essential role in spermatogenesis. Recently a study has shown that the mRNA of KDM4D is the key to the successful clone of the Macaque monkeys named as "Zhongzhong" and "Huahua, " which greatly increased pregnancy rates of female monkey, suggesting that the KDM4D gene may be strongly associated with reproduction. Therefore, the objective of this study was to explore possible single nucleotide polymorphisms (SNPs) within the coding region of KDM4D gene and analyze the associations with testis morphology traits of male pigs. Herein, two SNPs in exon1 of pig KDM4D gene were identified（NC_010451.4:g.1078A > G and NC_010451.4:g.1358G > C）. Among them, the g.1078A > G mutation was located at the JmjN domain which located from 15 to 55 amino acids of KDM4D. Association analyses showed that the g.1078A > G mutation was strongly associated with testis long circumference (TLC), testis short girth (TSG) and testis weight (TW) of Large White (LW) as well as Landrace (LD) ( p  < 0.05). The AA/AG genotype had a positive effect on testis morphology traits. Briefly, the novel missense mutation g.1078A > G could be a molecular marker for improving testis morphology traits in pig breeding.